Psychometric evaluation of the Farsi version of the Self-Care of Coronary Heart Disease Inventory version 3 - Negin Dorri; Sogol Olamazadeh; Gholamali Afrooz; Feridoun Noohi; Reza Pourhosein (Chronic Diseases Journal, 2024)
BACKGROUND: The Self-Care of Coronary Heart Disease Inventory -Patient Version 3 (SC-CHDI v3) is a globally used tool for assessing self-care behaviors among patients with coronary heart disease (CHD). This study aimed to translate the SC-CHDI v3 into Farsi, validate it, and evaluate its psychometric properties among Iranian patients.